The effect of a transition into poverty on child and maternal mental health: a longitudinal analysis of the UK Millennium Cohort Study - Dr Sophie Wickham, PhD; Prof Margaret Whitehead, PhD; Prof David Taylor-Robinson, PhD; Ben Barr, PhD (Elsevier, 2017)
Background: Whether or not relative measures of income poverty effectively reflect children's life chances has been the focus of policy debates in the UK. Although poverty is associated with poor child and maternal mental health, few studies have assessed the effect of moving into poverty on mental health. To inform policy, we explore the association between transitions into poverty and subsequent mental health among children and their mothers. Methods: In this longtitudinal analysis, we used data from the UK Millennium Cohort Study, a large nationally representative cohort of children born in the UK between Sept 1, 2000, and Jan 11, 2002, who participated in five survey waves as they progressed from 9 months of age to 11 years of age. Our analysis included all children and mothers who were free from mental health problems and not in poverty when the children were aged 3 years. We only included singletons (ie, not twins or other multiple pregnancies) and children for whom the mother was the main respondent to the study. The main outcomes were child socioemotional behavioural problems (Strengths and Difficulties Questionnaire) at ages 5 years, 7 years, and 11 years and maternal psychological distress (Kessler 6 scale). Using discrete time-hazard models, we followed up families without mental health problems at baseline and estimated odds ratios for subsequent onset of maternal and child mental health problems associated with first transition into poverty, while adjusting for confounders, including employment transitions. We further assessed whether or not change in maternal mental health explained any effect on child mental health. Findings: Of the 6063 families in the UK Millennium Cohort study at 3 years who met our inclusion criteria, 844 (14%) had a new transition into poverty compared with 5219 (86%) who remained out of poverty. After adjustment for confounders, transition into poverty increased the odds of socioemotional behavioural problems in children (odds ratio 1·41 [95% CI 1·02-1·93]; p=0·04) and maternal psychological distress (1·44 [1·21-1·71]; p<0·0001). Controlling for maternal psychological distress reduced the effect of transition into poverty on socioemotional behavioural problems in children (1·30 [0·94-1·79]; p=0·11). Interpretation: In a contemporary UK cohort, first transition into income poverty during early childhood was associated with an increase in the risk of child and maternal mental health problems. These effects were independent of changes in employment status. Transitions to income poverty do appear to affect children's life chances and actions that directly reduce income poverty of children are likely to improve child and maternal mental health. Funding: The Wellcome Trust and The Farr Institute for Health Informatics Research (Medical Research Council).